Implementasi Pendidikan Agama Kristen Melalui Family Education - Erwin Zai; Yanuar Ada Zega; Nikarni Zai (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Implementation of PAK through family education is really very important to do. To describe the implementation of PAK in the family, the authors use library research as a method. The background of this research is because there are obstacles in the process of applying PAK in families that are affected by the weakening of parents as educational figures. Of the many, one of the causes of PAK not manifesting satisfactorily in the family is parents who have not yet been born again. It means that parents still don't really think about themselves as disciples of Christ and feel that they are the main and first educators in the family. For this reason, parents must be aware that actualizing PAK in the family is their responsibility. Realizing effective PAK in the family, parents must educate their family members that PAK has a role and function as a change carrier that is dynamic, progressive, and transformative towards spiritual growth and development. The research carried out aims to contribute ideas to the problem of implementing PAK in families that have not been realized satisfactorily. The final conclusion of this article is that the implementation of PAK through family education is very much needed by today's Christian families.